Impact of a sodium carbonate spray combined with professional oral hygiene procedures in patients with Sjögren's syndrome: an explorative study. (4th November 2016) - Gambino, Alessio; Broccoletti, Roberto; Cafaro, Adriana; Cabras, Marco; Carcieri, Paola; Arduino, Paolo G.
Abstract : Objectives: The aim of this study was to make an initial estimation on the effects of a sodium bicarbonate and xylitol spray (Cariex ® ), associated with non‐surgical periodontal therapy, in participants with primary Sjögren's syndrome. Background: Sjögren's syndrome (SS) is a multisystem autoimmune disease that predominantly involves salivary and lachrymal glands, with the clinical effect of dry eyes and mouth. Materials and methods: A prospective cohort of 22 women and two men has been evaluated. They were randomized into three groups (eight patients each): Group A) those treated once with non‐surgical periodontal therapy, education and motivation to oral hygiene, associated with the use of Cariex ® ; Group B) treated only with Cariex ® ; Group C) treated only with non‐surgical periodontal therapy, education and motivation to oral hygiene. Clinical variables described after treatment were unstimulated whole salivary flow, stimulated whole salivary flow, salivary pH, reported pain (using Visual Analogue Scale) and the Periodontal Screening and Recording index. Results: Salivary flow rate improved in all groups, but the difference was statistically significant only in those treated with Cariex ®, alone or in combination with periodontal therapy. Gingival status improved in participants who underwent periodontal non‐surgical therapy while remained unchanged in those only treated with Cariex ® . Reported pain decreased in all groups, showing the best result in participants treated with periodontal therapy together with Cariex ® . Conclusions: We propose a practical approach for improving gingival conditions and alleviating oral symptoms in patients with SS. Future randomized and controlled trials are however required to confirm these results as well as larger population, and also assessing other parameters due to oral dryness, possible oral infections and more comprehensive periodontal indices.